2018
DOI: 10.1080/14789450.2018.1444483
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic approaches to identify blood-based biomarkers for depression and bipolar disorders

Abstract: Major depressive disorder (MDD) and bipolar disorder (BD) are leading causes of disability worldwide, yet many people remain undiagnosed, are misdiagnosed, and/or ineffectively treated. Diagnosis relies on the clinical assessment of symptoms, and there is currently no molecular or brain-imaging diagnostic test available. Identifying and validating protein biomarkers could provide a more accurate and objective means of diagnosis. Areas covered: Proteomics is a powerful tool that enables the identification and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…Although these studies have shown some promising results, they also demonstrated the importance of focusing on -omics that are more reflective of the functions and phenotypes of an individual [12,13]. Traditionally, studies have focused on the central nervous system (post-mortem brain tissues and cerebrospinal fluid), but this is practically challenging in clinical practice because of invasiveness and accessibility issues [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies have shown some promising results, they also demonstrated the importance of focusing on -omics that are more reflective of the functions and phenotypes of an individual [12,13]. Traditionally, studies have focused on the central nervous system (post-mortem brain tissues and cerebrospinal fluid), but this is practically challenging in clinical practice because of invasiveness and accessibility issues [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies to quantitatively measure peripheral protein profiles that are associated with mood disorders have increased [12][13][14]. Analysing the protein profiles of BD and differentiating them from those of MDD, in particular, can increase the understanding of disease pathophysiology and help us to distinguish these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…To detect this hypothesis, omics technologies, such as metabolomics and proteomics, have been applied as newfangled means to verify molecular profiling, characterize complex biological mechanisms, identify disease biomarkers, and determine pathophysiological processes in various disease states (Arnett and Claas, 2018). Employing omics approaches, some previous reports have performed a series of preclinical (Rao et al, 2016;Zhou et al, 2016;Karisetty et al, 2017) and clinical (Hashimoto, 2018;Preece et al, 2018;Schubert et al, 2018) investigations on depression. To gain insight into the pathogenesis of depression, metabolomics of the PFC and hypothalamus in inflammation-associated depression mouse model were performed in our previous studies (Wu et al, 2016(Wu et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to univariate methods that assess the differential expression of proteins on a single feature level, multivariate classification methods such as regularized logistic regression allows for establishing a prediction model based on samples with known class outcomes, e.g., remission versus non-remission 40 . A set of clinical and biological variables with the best joint discriminatory ability to differentiate between classes could be identified, and the resulting prediction model could then be used to predict the class outcomes of new patient samples.…”
Section: Soluble Serum Biomarkers Did Not Predict Remission In Non-stmentioning
confidence: 99%